The effects of WWP1 overexpression on the golgi apparatus stress response and proteoglycan production in adipocytes - Yuka Nozaki; Fumika Suwa; Kazuhiro Furuya; Masahiro Komeno; Shunsuke Hoshino; Yuhei Mizunoe; Kyohei Higashi; Masaki Kobayashi; Yoshikazu Higami (Scientific Reports)
Abstract White adipocytes are a major component of white adipose tissue (WAT) and help to maintain systemic metabolic homeostasis by storing energy and secreting adipokines. In mice deficient in the protein WWP1 (WW domain-containing E3 ubiquitin protein ligase 1), oxidative stress in adipocytes increases but insulin resistance induced by obesity improves. However, the specific roles of WWP1 in adipocytes remain unclear. Here, we show that in 3T3L1 adipocytes, WWP1 localized in the Golgi apparatus via its C2 domain, where it protected the Golgi apparatus from monensin-induced disruption. By contrast, WWP1 knockdown by short hairpin RNA failed to protect the Golgi apparatus and enhanced Golgi apparatus disruption by monensin. The Golgi apparatus acts as a central organelle to establish accurate protein glycosylation of proteoglycans containing glycosaminoglycans, including chondroitin sulfate and heparan sulfate (HS). WWP1 overexpression increased chondroitin sulfate and HS levels, whereas WWP1 knockdown decreased them. Furthermore, obesity-related increases in HS were prevented by WWP1 knockout in adipose tissue. In summary, our results demonstrate a novel role for WWP1 in maintaining Golgi apparatus morphology and proteoglycan synthesis in adipocytes.